(untitled) (Medical Forum Monthly, 2024)
Objective: Objective of this study is to compare the effect of ringer lactate and balanced salt solution on endothelial cell count after Phacoemulcification on larger sample size. Study Design: Randomized Control Trial Study Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Nishtar Medical College & Hospital Multan from December 2009 to May 2011. Materials and Methods: In this study, total 2902 eyes were included. 1453 were included in group A (where RL was used as irrigating fluid) and 1449 were included in group B (where BSS was used as irrigating fluid). The patients were examined on Day 1, and at one and three months. At each follow-up visit, corneal clarity was noted as the presence or absence of Descement’s folds and intra-stromal or epithelial edema. Anterior chamber was examined for the signs of inflammation as flare and cells. At three months follow-up, specular microscopy was performed. These examinations were done by the same observer who performs the tests preoperatively. Results: It was found that mean endothelial loss in total population was 310.471±163.055 with SE 3.036 while in group A it was 321.592±171.620 with SE 4.523. Endothelial cell loss in group B was found to be 299.380±153.292 with standard error 4.034. Percentage decrease in endothelial cell count in group A was 13.40% while in group B it was 12.54%. Difference in percentage loss of endothelial cell count between two groups was 0.86%. Conclusion: It is found that BSS is better solution for irrigation during intra-operative use during phacoemulsification than ringer lactate.